(untitled) (Avocetta, 2021)
The paper explores the application of the Swiss Cheese Theory (‘linear accident causation model’) to a local conservation project as a study case: i.e. the construction of a supplementary feeding station to support a local Black Kite Milvus migrans breeding population in a nature reserve of central Italy. In this regard, the project brings light to the conditioning factors (and related ‘slices’) that may be more critical when planning a conservation project. This experience provided valuable lessons in regards to conservation: (i) the authorization process (and related bureaucracy) represented the most challenging obstacle for the promoters and slowed down the project; (ii) the authorization process was easier and faster for a research project that anyway implied providing food to Black Kites; (iii) highly motivated volunteers and expert researchers made the difference; (iv) the use of the ‘effectiveness trajectories’ in conservation projects may highlight critical points, suggesting changes in strategy and facilitating the adaptive improvement of the project.